2014
DOI: 10.4236/jbnb.2014.53022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Synergistic Effects of Antibiotics with Triangular Shaped Silver Nanoparticles, Synthesized Using UV-Light Irradiation, on <i>Staphylococcus aureus</i> and <i>Pseudomonas aeruginosa</i>

Abstract: In the present work, a comparative study of antibacterial activity and synergistic effects of triangular silver nanoparticles in combination with two standard antibiotics is discussed for Staphylococcus aureus and Pseudomonas aeruginosa. A green route was developed to synthesise silver nanoparticles in which silver oxalate was taken as precursor, black tea leaves extract as surfactant and chitin as a stabilizing agent. A grey coloured colloidal solution of silver nanoparticles was obtained which was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In contrast, the antibacterial effect of silver triangles has been studied in greater details, with multiple studies identifying that the shape of prismatic (or triangular) particles playing a vital role in their high antibacterial activity. Although spherical particles are known to enter the cell preferentially and in higher numbers, the geometry of prismatic particles has been hypothesized to cause higher levels of toxicity because of disruption and damage to the cell membrane and cellular structure which occurs after internalization of the particles. , Although the likelihood that slowly diffusing AuNPs could cause membrane damage remains to be proven, further experimental work accompanied with appropriate modeling studies must be performed to more clearly understand the impact of particle geometry on intracellular damage. It is also possible that this effect relates to the differences in the exposed crystal planes in different morphologies and their influence on AuNP–protein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the antibacterial effect of silver triangles has been studied in greater details, with multiple studies identifying that the shape of prismatic (or triangular) particles playing a vital role in their high antibacterial activity. Although spherical particles are known to enter the cell preferentially and in higher numbers, the geometry of prismatic particles has been hypothesized to cause higher levels of toxicity because of disruption and damage to the cell membrane and cellular structure which occurs after internalization of the particles. , Although the likelihood that slowly diffusing AuNPs could cause membrane damage remains to be proven, further experimental work accompanied with appropriate modeling studies must be performed to more clearly understand the impact of particle geometry on intracellular damage. It is also possible that this effect relates to the differences in the exposed crystal planes in different morphologies and their influence on AuNP–protein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, synergistic activity of triangular shaped silver nanoparticles along with antibiotics ampicillin and gentamicin was studied against Staphylococcus aureus and Pseudomonas aeruginosa. In that study triangular nanoprism with sharp vertices and edges displays higher antibacterial activity in comparison to other shapes of silver nanoparticles which finds these nanoparticles useful for biomedical applications [23]. Vivekanandan et al was also reported the synergistic antibacterial activity of cephalexin with Ag NPs [9].…”
Section: Resultsmentioning
confidence: 99%
“…Triangular silver nanoparticles (50 nm) synthesized using green technology had an equal effect against Staphylococcus aureus and Pseudomonas aeruginosa. Green technology for synthetic silver nanoparticles has become a significant research trend (Saha, Malik, & Qureshi, 2014).…”
Section: Introductionmentioning
confidence: 99%